A avaliação e os processos de ensino e de aprendizagem no contexto universitário : um estudo de caso - Diniz, Ana Aleixo (2009)
The word assessment has different meanings and it has no difference when we think of the act of evaluating in the educational context. It can be used as a means of classification, exclusion or as a very useful tool in the teaching-learning process. This work is a case study that has as a landscape a particular subject in the Physics Course of a Public University in Sao Paulo State and the subjects are its professors and students. This study, presenting as methodology the approach of a study-case, has different collect tools and it shows the relationship between assessment and the teaching-learning process by diverse perspectives. Two important conclusions can be drawn from this study: the first one is that the educator s conceptions of assessment and the teachinglearning process have a direct influence on the relations that will be established within the assessment along the subject teaching. The university context brings up some particularities and the university educator is set aside in this study-case. The second important consideration is the way that the study approaches the teacher and it can discuss about issues related to content s pedagogical aspects, a way to achieve the university educator.